2008
DOI: 10.1111/j.1524-475x.2008.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of topical negative pressure in wound repair: Expression of biochemical markers in wound fluid during wound healing

Abstract: The clinical effects of topical negative pressure therapy (TNP) on wound healing are well described in numerous articles. While the mechanism(s) of action are not completely understood, it is postulated that reduction of local and interstitial tissue edema, increased perfusion of the (peri-) wound area, changed bacterial composition, and mechanical stimulation of the woundbed contribute to the clinical success. Our hypothesis is that with the removal of excessive fluid, proteolytic enzymes negatively influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…Wound fluid samples were collected daily for up to 10 days using a sterile porous filter, and quantitative measurements of pro-MMP-9 and TIMP-1 levels were analyzed using enzyme-linked immunosorbent assay (ELISA). 23 Stechmiller et al reported significant decreased tumor necrosis factor-a levels after 7 days of NPT in six patients with pressure ulcers. Instead, they did not find decreased levels of interleukin-1b (IL-1b), MMP-2, MMP-3, or TIMP-1 from the baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound fluid samples were collected daily for up to 10 days using a sterile porous filter, and quantitative measurements of pro-MMP-9 and TIMP-1 levels were analyzed using enzyme-linked immunosorbent assay (ELISA). 23 Stechmiller et al reported significant decreased tumor necrosis factor-a levels after 7 days of NPT in six patients with pressure ulcers. Instead, they did not find decreased levels of interleukin-1b (IL-1b), MMP-2, MMP-3, or TIMP-1 from the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34] Nevertheless only few articles described the NPT influence on MMPs activity. [22][23][24][25] Greene et al described the reduction in MMP-9/ neutrophil gelatinase-associated lipocalin, MMP-9, latent, and active MMP-2 activity by 15% to 76% determined by zymography in three patients (1 DFU) after 2 weeks of NPT. 22 Moues et al showed significantly lower levels of pro-MMP-9 and higher ratio of MMP-9/TIMP-1 in 15 NPT-treated wounds than in 18 conventional treated wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In our country, pressure values usually range from 120 to 125 mmHg, as this value is conducive to granulation growth (Mouës et al, 2008). However, there have been reports regarding the application of higher negative pressures (450-600 mmHg) (Morykwas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years this technique has experienced rapid development and has been widely used to treat various acute and chronic wounds with excellent outcomes (Gabriel et al, 2009;Witkowski et al, 2009;Palm et al, 2011;Wood and Molnar, 2011;Masden et al, 2012;Ogawa, 2012). Both locally and abroad, the VAC mechanism has attracted a great deal of research, and results show that VAC plays various roles in wound healing: cleaning of wound exudate, reduction of peripheral edema, improvement of local blood supply, removal of bacteria, inhibition of bacterial proliferation, acceleration of granulation growth, and re-epithelialization (Sexena et al, 2004;Labler et al, 2006;Mouës et al, 2008;Chan, 2009;Parker, 2012;Chen et al, 2013;Dong et al, 2013). Thus, this technique can shorten wound healing time and provide a bed for delayed skin grafts.…”
Section: Introductionmentioning
confidence: 99%
“…SPT assists in the evolution of the wound through several mechanisms: it reduces of local edema 7 , provides wound contraction, stimulates neoangiogenesis, removes exudate 8 , improves blood flow 9 and reduces bacterial colonization 10 . Many of these effects are desirable for the treatment of large traumatic wounds to the limbs, especially the reduction of edema and improvement of blood flow to the wound and to rotated flaps.…”
mentioning
confidence: 99%